Analisis Yuridis Terhadap Pemberian Asimilasi Narapidana Menurut Peraturan Menteri Hukum dan Hak Asasi Manusia Republik Indonesia Nomor 10 Tahun 2020 Ditinjau dari Tujuan Pemidanaan - Yosef Mattew Nathanael; Maria Maya Lestari; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The number of prisoners has exceeded the capacity of prisons, then the government made emergencyeffort to prevent the spread of the Covid-19 by stipulating the Regulation of the Minister of Law and HumanRights Number 10 of 2020 concerning Requirements for Assimilation anf Integration Rights for Prisonersand Children in the Framework of Prevention and Control of Covid-19. The principle of assimilation is tointegrate prisoners into society, in the hope of regaining confidence and always applying the principle ofgood behavior. Meanwhile, during the assimilation of Covid-19, there is still a repetition of criminal actsafter assimilation’s given, so the principle of assimilation is considered not achieved in society. The purposeof writing this thesis, as follows; First, Legal problems that arise after providing assimilation for prisonersaccording to the Regulation of the Minister of Law and Human Rights Number 10 of 2020 related to effortto prevent and control the spread of Covid-19 in Indonesia, Second, The ideal concept of providingassimilation of prisoners during the Covid-19 pandemic in the correctional system to achieve the purpose ofpunishment.This type of research can be classified in the normative juridical type of research, because the authorexamines law from an internal perspective with the object of research being legal norms. The author uses alegislative approach carried out by reviewing ministerial regulations related to legal issues. The datasources used are primary data, secondary data, and tertiary data. Data collection techniques in this studyare in the form of literature studies.From the results of problem research there are two main things that can be concluded. First, Legalproblems that arise after providing assimilation for prisoners according to the Regulation of the Minister ofLaw and Human Rights Number 10 of 2020 related to effort to prevent and control the spread of Covid-19in Indonesia, the legal problem that arise are not carrying out the rules for assimilation requirements athome, repetition of criminal acts, and the gap between the implementation of Covid-19 assimilation andpublic reaction. Second, The ideal concept of providing assimilation of prisoners during the Covid-19pandemic in the correctional system to achieve the purpose of punishment, that prisoners who commit drugcrimes by distributing narcotics don’t need to be assimilated at home and it would be nice if health agenciesand labor agencies were involved in assimilation. The author’s suggestion is, First, a strict monitoring andmonitoring mechanism is needed for assimilated prisoners, as well as transparent and fair implementationso as not to violate legal and human rights principles. Second, that the development of prisoners is expectedto improve the quality of the coaching program, continue to involve the community, increase evaluation, andexpand cooperation.Keywords: Assimilation, Inmate, Covid-19, Purpose of Punishment.